2022
DOI: 10.3389/fgene.2022.983811
|View full text |Cite
|
Sign up to set email alerts
|

The application of short and highly polymorphic microhaplotype loci in paternity testing and sibling testing of temperature-dependent degraded samples

Abstract: Paternity testing and sibling testing become more complex and difficult when samples degrade. But the commonly used genetic markers (STR and SNP) cannot completely solve this problem due to some disadvantages. The novel genetic marker microhaplotype proposed by Kidd’s research group combines the advantages of STR and SNP and is expected to become a promising genetic marker for kinship testing in degraded samples. Therefore, in this study, we intended to select an appropriate number of highly polymorphic SNP-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For our 50-plex MH panel, Het values of more than 98% (49/50) of MHs were >0.40, A e values of more than 80% (40/50) MHs > 3.0, and CDP and CPE were 1–3.109 × 10 −49 and 1–8.727 × 10 −16 , respectively ( Supplementary Table S4 ). The results showed that our panel has surpassed the capacity of commonly used 23 STRs [ 50 , 51 ] or 52 SNPs [ 52 ] and several other reported MH panels [ 30 , 53 ], indicating that our panel could be potentially effective for future applications in individual identification, kinship testing, mixture interpretation, and non-invasive prenatal paternity testing (NIPPT) [ 3 , 42 ].…”
Section: Discussionmentioning
confidence: 89%
“…For our 50-plex MH panel, Het values of more than 98% (49/50) of MHs were >0.40, A e values of more than 80% (40/50) MHs > 3.0, and CDP and CPE were 1–3.109 × 10 −49 and 1–8.727 × 10 −16 , respectively ( Supplementary Table S4 ). The results showed that our panel has surpassed the capacity of commonly used 23 STRs [ 50 , 51 ] or 52 SNPs [ 52 ] and several other reported MH panels [ 30 , 53 ], indicating that our panel could be potentially effective for future applications in individual identification, kinship testing, mixture interpretation, and non-invasive prenatal paternity testing (NIPPT) [ 3 , 42 ].…”
Section: Discussionmentioning
confidence: 89%
“…However, its limitations become apparent with those STRs not only in cases involving the determination of relationships with distant degrees (e.g., second-cousins) but also in complex relationships. For example, it is challenging to distinguish full-siblings from half-siblings using autosomal STRs and a standard LR approach (Wen et al 2022 ). However, the ICS-based approach offers a valuable means of determining a relationship based on the calculated ICS value without the need for assumptions about the alleged relationship when evaluating genetic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of DNA sequence polymorphism has been enhanced, and the exploration of novel genetic markers is steadily advancing. The advantages of MHs in the fields of mixture deconvolution ( Oldoni et al, 2020 ; Tao et al, 2022 ; Yu et al, 2022 ), biogeographic ancestry inference ( de la Puente et al, 2020 ; Tao et al, 2022 ), complex kinship analysis ( Wen et al, 2022 ; Xue et al, 2023 ) and personal identification ( Pu et al, 2017 ) have been extensively investigated. Based on NGS, FGG has played a significant role in identifying unknown remains ( Bertoglio et al, 2020 ), inferring distant relatives ( Kling et al, 2021 ), and solving cold cases ( Phillips, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mixed samples pose additional challenges during analysis due to a higher probability of drop-out or drop-in combined with stutter peak ( Gill et al, 2012 ; Bai et al, 2022 ). To overcome these hurdles, MHs have been extensively studied by scholars due to their combined advantages of STR and SNP markers, such as low mutation rate, high polymorphism, short length, and absence of stutter peaks ( Kidd et al, 2013 ; Oldoni et al, 2019 ; Bai et al, 2022 ; Wen et al, 2022 ). Bai et al developed a large panel consisting of 185 MHs to analyze degraded and/or mixed DNA samples demonstrating its utility in conducting parentage, full sibling, and second-degree relative testing, but improvements are necessary to infer more distant relatives (third-degree relatives) ( Bai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%